Digital cataloguing and classification - Shah, Mohammad Muzafar (New Delhi Rajat Publications, 2024)
The Present book is designed to furnish valuable information on both general and specific aspects of cataloguing and classification for all forms of digital library materials.
Keywords: Library and Information Science; Cataloguing and Classification